A Study On Academicians’ Turnover Intention In Higher Learning Institution - Lim, Geok May (Universiti Malaysia Sarawak, UNIMAS, 2011)
Employee is the asset for an organization to move forward. It is seen as the “blood” for an organization in order to success. Employees fall under two categories, which are satisfied employees and unsatisfied employees. Satisfied employees generally tend to be more productive as compared to the unsatisfied employees (Oshabemi, 20002; Hom and Gritteth, 1995). Therefore, satisfaction of the academicians is crucial because it is the determinant of the actual turnover for an organization. Factors which contribute to the employees job satisfaction would be determine as it would affect the intention to turnover in an organization.